Impacts of essential amino acids on energy balance - Fei Xiao; Feifan Guo (Elsevier, 2022)
Background: Obesity develops due to an imbalance in energy homeostasis, wherein energy intake exceeds energy expenditure. Accumulating evidence shows that manipulations of dietary protein and their component amino acids affect the energy balance, resulting in changes in fat mass and body weight. Amino acids are not only the building blocks of proteins but also serve as signals regulating multiple biological pathways. Scope of review: We present the currently available evidence regarding the effects of dietary alterations of a single essential amino acid (EAA) on energy balance and relevant signaling mechanisms at both central and peripheral levels. We summarize the association between EAAs and obesity in humans and the clinical use of modifying the dietary EAA composition for therapeutic intervention in obesity. Finally, similar mechanisms underlying diets varying in protein levels and diets altered of a single EAA are described. The current review would expand our understanding of the contribution of protein and amino acids to energy balance control, thus helping discover novel therapeutic approaches for obesity and related diseases. Major Conclusions: Changes in circulating EAA levels, particularly increased branched-chain amino acids (BCAAs), have been reported in obese human and animal models. Alterations in dietary EAA intake result in improvements in fat and weight loss in rodents, and each has its distinct mechanism. For example, leucine deprivation increases energy expenditure, reduces food intake and fat mass, primarily through regulation of the general control nonderepressible 2 (GCN2) and mammalian target of rapamycin (mTOR) signaling. Methionine restriction by 80% decreases fat mass and body weight while developing hyperphagia, primarily through fibroblast growth factor 21 (FGF-21) signaling. Some effects of diets with different protein levels on energy homeostasis are mediated by similar mechanisms. However, reports on the effects and underlying mechanisms of dietary EAA imbalances on human body weight are few, and more investigations are needed in future.